How Many Es? What Must Public Administrators Consider in Providing for the Public Good?. (4th May 2022) - Norman-Major, Kristen
Abstract: Scholars and practitioners of public administration often discuss the core values of the field. Referred to as the pillars of public administration, economy, efficiency, effectiveness and equity have been raised as the 4 Es essential to the practice of public administration. In her 2011 article, "Balancing the 4Es: or Can We Achieve Equity for Social Equity in Public Administration?, " Norman-Major asks if social equity had been raised to the same status as economy, efficiency and effectiveness. This article re-examines that question along with the suggestion of the symposium editors that there should be a new set of Es: engagement, empathy, equity and ethics. The author concludes that all seven of the Es are important to consider in the practice of public administration.